The financial crisis as a wake-up call: corporate governance and bank performance in an emerging economy. Issue 1 (24th September 2018) - Orazalin, Nurlan; Mahmood, Monowar
Abstract : Purpose: This paper aims to investigate the effects of different sets of corporate governance (CG) practices on bank performance before, during and after the financial crisis. The study proposes some policy measures for improved CG practices to protect banks from the detrimental effects of future financial crises and economic meltdowns in the context of emerging markets such as Kazakhstan. Design/methodology/approach: The study analyses data from all commercial banks listed in Kazakhstan Stock Exchange for the pre-economic crisis, during the crisis and after the economic crisis periods. The study uses the panel regression model to control unobserved time-constant heterogeneity. Findings: The study found that better CG practices led to better operating performance of the banks after the financial crisis periods. The changes in CG codes, board structures, disclosure requirements and board members' competencies over time had a significant influence on CG practices and subsequently improved operating performance of the banks. Originality/value: This is one of the first studies to examine the effects of CG practices on bank performance in central Asian transition economies, which are still heavily influenced by Soviet heritage and legacy.